The Influence of the Implementation of Good Corporate Governance, Corporate Performance and Company Size on Disclosure of Corporate Social Responsibility - Fina Melinda Jumrotul Mu'minin; Dwi Asih Surjandari (Dinasti Publisher, 2023)
This study looks at how Good Corporate Governance, Company Performance and Company Size affect the disclosure of Corporate Social Responsibility (CSR) and how it affects investor reactions. By using secondary data in the form of annual reports and sustainability reports, . The total sampling used in this study were 14 companies. The software used is Eviews 12. This study found that the audit committee, return on assets and company size have an effect on CSR disclosure, while the board of independent commissioners has no effect. However, CSR disclosure has no impact on investor reactions.